Improved methods for fuzzy comprehensive evaluation of the reclamation suitability of abandoned mine lands. Issue 3 (3rd April 2017) - Cheng, Linlin; Hu, Zhenqi; Lou, Shang
Abstract: Division of evaluation units and establishment of membership functions are two key steps of fuzzy comprehensive reclamation suitability evaluation of abandoned mine lands. This paper improves both the method of evaluation units division and the method of membership functions establishment. Empirical research is carried out in Mentougou district of Beijing in China. It shows that as a mountainous area, among the 603.79 hm 2 abandoned mine lands in Mentougou, highly and moderately suitable area for agriculture use are only 54.99 hm 2 and 80.00 hm 2 . Lowly suitable area is 468.80 hm 2 . This research can provide theoretical support for the practice of abandoned mine lands reuse.